Recognition of ZnT8, Proinsulin, and Homologous MAP Peptides in Sardinian Children at Risk of T1D Precedes Detection of Classical Islet Antibodies - Magdalena Niegowska; Daniela Paccagnini; Carla Mannu; Clara Targhetta; Marco Songini; Leonardo A. Sechi (Journal of Diabetes Research)
As numerous studies put in evidence the increasing incidence of type 1 diabetes (T1D) in children, an early diagnosis is of great importance to define correct treatment and diet. Currently, the identification of classical islet autoantibodies is the primary biomarker for diagnosis in subjects at risk, especially in pediatric patients. Recent studies suggest that detection of antibodies against ZnT8 protein in preclinical phase can predict the development of T1D. We previously demonstrated a significant association of Mycobacterium avium subspecies paratuberculosis (MAP) with T1D in adult Sardinian patients. To enforce this finding, we investigated the presence of antibodies against ZnT8 and proinsulin (PI) with respective homologous epitopes: MAP3865c133–141/ZnT8186–194, MAP3865c125–133/ZnT8178–186, MAP2404c70–85/PI46–61, and MAP1,4αgbp157–173/PI64–80, in 23 children at risk for T1D, formerly involved in the TRIGR study, and 22 healthy controls (HCs). Positivity to anti-MAP and homologous human peptides was detected in 48% of at-risk subjects compared to 5,85% HCs, preceding appearance of islet autoantibodies. Being MAP easily transmitted to humans with infected cow’s milk and detected in retail infant formulas, MAP epitopes could be present in extensively hydrolyzed formula and act as antigens stimulating β-cell autoimmunity.